Carbon Dots Derived from Waste Fish Scale for Enhanced Removal of Levofloxacin Drug: Parametric Optimization, Isotherm and Kinetic Studies - Olateju, Idowu Iyabo; Adeyi, Abel Adekanmi; Giwa, Abdulwahab (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The public health and environmental protection have been facing a great challenge for efficient antibiotics’ adsorption from aqueous solution. In this work, a carbon dots nanoparticle from biomass (fish scale) was synthesized and employed for antibiotic adsorption. The synthesized fish scale carbon dots (FCD) were characterized by means of the X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier transform infrared (FTIR) analyses. Experiments on adsorption were performed to examine the capability of the synthesized adsorbent for adsorption of Levofloxacin. The optimum conditions were ascertained through the use of Response Surface Methodology (RSM) design to increase the effectiveness of levofloxacin removal, and there was 96.03% removal efficiency of 60 minutes contact time, 10 mg/L levofloxacin concentration and FCD dosage of 0.2 g/L. Also, the adsorption experiments indicated that at the lowest concentration of 10 mg/L, at time 45 min and 0.15 mg dosage the adsorption rate was high. For the kinetics data, the pseudo-second order model best fit the data. Furthermore, the Redlich-Peterson model fit isothermal data the best.